2018
DOI: 10.1016/j.bbmt.2017.12.784
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Consolidation Is Not Beneficial for Adults with ALL Undergoing Myeloablative Allogeneic Transplantation

Abstract: Allogeneic hematopoietic cell transplantation (alloHCT) is curative for patients with acute lymphoblastic leukemia (ALL) who achieve complete remission (CR1) with chemotherapy. However, the benefit of consolidation chemotherapy remains uncertain in patients undergoing alloHCT. We compared clinical outcomes of 524 adult patients with ALL in CR1 who received ≥2 (n = 109), 1 (n = 93), or 0 cycles (n = 322) of consolidation before myeloablative alloHCT from 2008 to 2012. As expected, time to alloHCT was longer wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…A large analysis of Center for International Blood and Marrow Transplant Research data on 524 ALL patients demonstrated that chemotherapy provided no Values are n (%). apparent advantage for CR1 patients with an immediately available donor considered for a prompt myeloablative allo-HSCT [28]. Moreover, additional intensive chemotherapy might not always reduce the leukemia burden because of enhanced resilience of leukemia cells that survive the multiagent regimens [29].…”
Section: Discussionmentioning
confidence: 99%
“…A large analysis of Center for International Blood and Marrow Transplant Research data on 524 ALL patients demonstrated that chemotherapy provided no Values are n (%). apparent advantage for CR1 patients with an immediately available donor considered for a prompt myeloablative allo-HSCT [28]. Moreover, additional intensive chemotherapy might not always reduce the leukemia burden because of enhanced resilience of leukemia cells that survive the multiagent regimens [29].…”
Section: Discussionmentioning
confidence: 99%
“…These data will help determine which therapies should be applied as a bridge to transplantation and which therapies in selected patients may supplant allo-HCT. Pre-HCT bridging therapy, including additional pre-HCT consolidation [119], might increase toxicities such as GVHD and veno-occlusive disease, when these therapies are used sequentially. Targeted and immune therapies may also have an expanding role for patients with MRD after allo-HCT.…”
Section: Areas Of Needed Researchmentioning
confidence: 99%
“…Even if HSCT is curative for an ALL patient in CR1, the benefits of consolidation chemotherapy do not appear to add any significant benefit for patients with available donors who undergo a myeloablative HSCT, as proven by the study coordinated by Weisforf et al [89]. In 524 adult patients with ALL in CR1 who received at least two, one, or no cycles of consolidation before myeloablative HSCT from 2008 to 2012, those receiving at least two, one, or no cycles of consolidation had an adjusted 3-year cumulative incidence of relapse of 20%, 27%, and 22%.…”
Section: Allogeneic Stem Cell Transplantation For Allmentioning
confidence: 99%